2008
DOI: 10.1590/s0004-28032008000200006
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of red-hot chili pepper increases symptoms in patients with acute anal fissures. A prospective, randomized, placebo-controlled, double blind, crossover trial

Abstract: -Background -Red-hot chili pepper and other spices have been blamed for causing or exacerbating symptoms of anal pathologies like anal fissure and hemorrhoids. Aim -To determine if consumption of chilies increases symptoms of acute anal fissures. Methods -Individual patients were randomized to receive capsules containing chili or placebo for one week in addition to analgesics and fiber supplement. Patients were asked to note score for symptoms like pain, anal burning, and pruritus during the study period. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…can aggravate symptoms in patients with acute fissure in ano. 13,22 In the study conducted by Chaudhary A et al, it was found that 98.6% of patients consumed mixed diet and 1.4% was purely vegetarians.…”
Section: Discussionmentioning
confidence: 99%
“…can aggravate symptoms in patients with acute fissure in ano. 13,22 In the study conducted by Chaudhary A et al, it was found that 98.6% of patients consumed mixed diet and 1.4% was purely vegetarians.…”
Section: Discussionmentioning
confidence: 99%
“…These results illustrate that the eye disease is, the less frequently seen and the hemorrhoid is the most ordinarily observed illness in the area. This high occurrence of hemorrhoid disease in the region may be caused with plenty of hot pepper consumption habits of the locals as a spice (Gupta, 2008) whereas the emergence of eye disease with the lowest level may be due to the fish intake rituals (Giovanni et al, 2009). …”
Section: Uv Data Analysismentioning
confidence: 99%
“…The fruit is characterized as a berry, deciduous or persistent that produces capsaicinoid metabolites (DE SMET, 1985). In addition to the application of pepper for culinary purposes, there was always an appreciation from the population for a belief that it would bring benefits in the treatment of hemorrhoids (GUPTA, 2008). However, these beliefs are not confirmed by the scientific community, as patients with hemorrhoids are advised to avoid foods with the potential to irritate such as peppers, coffees, colas, and spices (OHNING; MACHICADO;JENSEN, 2009); that is, their consumption is not recommended for patients with anal fissures because pepper seems to aggravate the condition of patients with acute anal fissures (ulcers).…”
Section: 'Evil Eye' On the Pepper Plantmentioning
confidence: 99%